Photonic Design, Verification, and Implementation: A look around at the European scene. Issue 4 (24th October 2018) - Gonzalez, Ana; Pozo, Jose
Abstract: The requirement of different sectors such as healthcare, telecommunications, and industry for new systems that will provide higher performance and lower foot‐print has triggered the development of many new photonic‐based solutions. A key aspect of the development of an optical system is the design and verification before its production to reduce failure and, as consequence, the time‐to‐market. There are commercial software solutions able to simulate and to analyze the packaging of optical systems, photonic integrated circuits (PICs) based devices, transmission systems & networks, and fiber‐optic lasers & amplifiers. Also, it is possible to take into account thermal and mechanical issues by multiphysics simulations. In this article, we explore the different available solutions to simulate your optical design before the production at the component level including free‐form optics and photonic integrated circuits (PICs) and also at the system level.